DIKLAT LEADERSHIP DAN ENTREPRENEURSHIP DI SMK NEGERI SUKAPURA PROBOLINGGO - Winarto, Bambang; Nuraina; Damayanti, Nia Wahyu (Jurnal Pengabdian Kepada Masyarakat Bersinergi Inovatif, 2024)
The implementation of community service through leadership and entrepreneurship training activities at Sukapura Probolinggo State Vocational School aims to increase teacher leadership and entrepreneurial capacity. This training helps teachers improve their competence in terms of leadership and entrepreneurship. These competencies are essential for managing the classroom, inspiring students, and managing school projects. We design this program to equip teachers with the practical and theoretical skills required to become effective leaders and successful entrepreneurs. The training methodology includes various approaches, such as lectures, group discussions, case studies, and business simulations. This activity involves collaboration between academics, business practitioners, and schools to provide a holistic and applicable learning experience. The results of this program show a significant increase in teachers' knowledge and skills related to leadership and entrepreneurship. Apart from that, this program also motivates teachers to develop their potential and prepares them to be able to educate the younger generation to face the challenges of the world of work and business in the future. Periodic program evaluations ensure the effectiveness and sustainability of this service activity